Empowering the Children...helping them Soar with Self-esteem - Aggarwal, Sheelu (THE PRIMARY TEACHER, 2006)
Whether it is adjusting to a different teaching style, juggling academic demands, or coping with peer pressure, most children find themselves facing difficult situations at school sometime during their academic career. While parents can’t (and shouldn’t) shield their children from these challenges directly, they can counsel them; the way a parent responds can make all the difference. Studies have found that children whose parents promote the child’s self-esteem tend to do better in school,are less likely to  succumb to negative peer pressure, and have the confidence to face life’s many challenges. Dr. Robert Brooks, a clinical professor of psychology at Harvard University Medical School and author of The Selfesteem Teacher says, “One of the most important things a parent can do is to be empathetic and to see the world through their child’s eyes. This is a basic skill parents need to promote because it will determine what you say to your child when they are having a problem.” The best thing parents can do if a child is experiencing difficulty is to recognise their child’s concerns and talk about them with the child. You need not promise that everything will be just fine. But doremind them of instances when they were